Analisis Pengaruh Jumlah Uang Beredar Terhadap Produk Domestik Bruto (PDB) Indonesia - Ulfa, Zakia Rahmania; Fisabilillah, Ladi Wajuba Perdini (Jurnal Ekonomika : INDEPENDEN, 2023)
Money, which functions as a transaction tool, can influence the dynamics of economic activity within a country. This study was conducted to reveal the impact of money in circulation on GDP in Indonesia during the period 1993-2022. The research method applied is a quantitative approach, with data obtained from the official BPS portal. The data analysis approach used time series techniques with simple linear regression. The findings of this study indicate that the money supply variable has a significant positive impact on GDP.